Influence of synthesis conditions on molecular weight as well as mechanical and thermal properties of poly(hexamethylene 2,5-furanate) - Paszkiewicz, Sandra; Irska, Izabela; Walkowiak , Konrad; Zubkiewicz , Agata (Polimery, 2021)
Poly(hexamethylene 2,5-furanate) (PHF) was obtained by melt polycondensation. The process was carried out at temperatures of 230, 235 and 240 ° C. It has been shown that the selection of the optimal parameters of the synthesis process leads to the obtaining of biomaterials of high molecular weight, and thus better mechanical and thermal properties. The relationship between the molecular weight and the mobility of polymer chains, and consequently the temperature of phase changes and mechanical properties, was determined.